Tissue plasminogen activator is a ligand of cation-independent mannose 6-phosphate receptor and consists of glycoforms that contain mannose 6-phosphate - Miller, James J. (Sci Rep, 2021)
Plasmin is the key enzyme in fibrinolysis. Upon interaction with plasminogen activators, the zymogen plasminogen is converted to active plasmin. Some studies indicate plasminogen activation is regulated by cation-independent mannose 6-phosphate receptor (CI-MPR), a protein that facilitates lysosomal enzyme trafficking and insulin-like growth factor 2 downregulation. Plasminogen regulation may be accomplished by CI-MPR binding to plasminogen or urokinase plasminogen activator receptor. We asked whether other members of the plasminogen activation system, such as tissue plasminogen activator (tPA), also interact with CI-MPR. Because tPA is a glycoprotein with three N-linked glycosylation sites, we hypothesized that tPA contains mannose 6-phosphate (M6P) and binds CI-MPR in a M6P-dependent manner. Using surface plasmon resonance, we found that two sources of tPA bound the extracellular region of human and bovine CI-MPR with low-mid nanomolar affinities. Binding was partially inhibited with phosphatase treatment or M6P. Subsequent studies revealed that the five N-terminal domains of CI-MPR were sufficient for tPA binding, and this interaction was also partially mediated by M6P. The three glycosylation sites of tPA were analyzed by mass spectrometry, and glycoforms containing M6P and M6P-N-acetylglucosamine were identified at position N448 of tPA. In summary, we found that tPA contains M6P and is a CI-MPR ligand.